2021
DOI: 10.1111/1462-2920.15749
|View full text |Cite
|
Sign up to set email alerts
|

The Azospirillum brasilense type VI secretion system promotes cell aggregation, biocontrol protection against phytopathogens and attachment to the microalgae Chlorella sorokiniana

Abstract: The plant-growth-promoting bacterium Azospirillum brasilense is able to associate with the microalgae Chlorella sorokiniana. Attachment of A. brasilense increases the metabolic performances of the microalgae. Recent genome analyses have revealed that the A. brasilense Az39 genome contains two complete sets of genes encoding type VI secretion systems (T6SS), including the T6SS1 that is induced by the indole-3-acetic acid (IAA) phytohormone. The T6SS is a multiprotein machine, widespread in Gramnegative bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 122 publications
(205 reference statements)
0
14
0
Order By: Relevance
“…An intriguing genomic feature of the two recovered MAGs in this study was the near-complete set of T6SS structure genes, in contrast to other genomes of Endozoicomonas retrieved from corals that did not carry either any or only one of the T6SS-like genes, although they are commonly detected in Endozoicomonas species from noncoral hosts. Bacterial T6SS is a common secretion system, detected in approximately 25% of all Gram-negative bacteria ( 37 ) and important for virulence traits in pathogenesis ( 38 ), bacterial communication ( 39 ), cell aggregate formations ( 40 ), and biofilm formation ( 41 ). Many plant pathogenic bacteria process the T6SS, producing the virulent effectors to eliminate their antagonists and suppress plant defenses, thereby allowing bacterial colonization in host tissues ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing genomic feature of the two recovered MAGs in this study was the near-complete set of T6SS structure genes, in contrast to other genomes of Endozoicomonas retrieved from corals that did not carry either any or only one of the T6SS-like genes, although they are commonly detected in Endozoicomonas species from noncoral hosts. Bacterial T6SS is a common secretion system, detected in approximately 25% of all Gram-negative bacteria ( 37 ) and important for virulence traits in pathogenesis ( 38 ), bacterial communication ( 39 ), cell aggregate formations ( 40 ), and biofilm formation ( 41 ). Many plant pathogenic bacteria process the T6SS, producing the virulent effectors to eliminate their antagonists and suppress plant defenses, thereby allowing bacterial colonization in host tissues ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also noteworthy that the presence or absence of T6SS, as well as its mutation, does not impact the transmission of S. rhizophila CFBP13503 when in competition with Xcc8004. Consequently, the T6SS of S. rhizophila CFBP13503 does not seem to be involved in its adhesion or colonization capacities of radish seed and seedling, unlike what has been observed in other bacterial species (Cassan et al, 2021; Mosquito et al, 2019).…”
Section: Discussionmentioning
confidence: 63%
“…Consequently, the T6SS of S. rhizophila CFBP13503 does not seem to be involved in its adhesion or colonization capacities of radish seed and seedling, unlike what has been observed in other bacterial species (Cassan et al, 2021;Mosquito et al, 2019). Russell et al, 2013) capable of lysing the membranes of target bacteria, DNases (Tde) that exhibit antibacterial properties by targeting nucleic acids, amidases (Tae) that degrade peptidoglycan to lyse the target bacterium, and potentially a pore-forming effector that inhibits the growth of target cells by depolarizing the inner membrane.…”
Section: -Discussionmentioning
confidence: 66%
“…Rather, our experiments suggest that diffusible metabolites from A. baldaniorum Sp245 reduce P. fluorescens A506 biofilm development (Figure 5). Azospirillum secreted factors, such as type 6 secretion system effectors (Cassan et al, 2021), bacteriocins or siderophores (Tapia-Hern andez et al, 1990), or interference with the quorum sensing (QS) process of pseudomonads by quenching the signals (Gualpa et al, 2019), are strong candidates to explain A506 growth restriction. This work revealed that the outcome of A. baldaniorum Sp245 and P. fluorescens A506 interaction in macrocolonies is highly dynamic in time and space and dependent on medium composition.…”
Section: Discussionmentioning
confidence: 99%